Social networking sites passive use and its effects on sad-happy mood - Tartaglia Stefano; Bergagna Elisa (Psihologija, 2022)
The social comparison theory explains some negative effect of social networking sites (SNSs) use. These Internet applications have made easier the online social comparison that in turn predicts depression and lower life satisfaction. Individuals prone to depression engage in greater levels of social comparison, particularly with others who are thought to be slightly better off, and experience a decrease in mood or self-esteem in the light of others’ perceived happiness. The present study aimed at investigating the impact of the use of SNSs on the mood in an experimental design. In total, 120 university students were randomly assigned to one of two groups. In the experimental groups, the participants were instructed to access their Facebook and browse personal profiles for 20 minutes; while in the control, they read articles. For the participants with initial low mood using Facebook further lowered their mood whereas for the other participants did not have any effect. Furthermore, using Facebook lowered the mood of the participants not accustomed to use it frequently.